Famotidine use and quantitative symptom tracking for COVID-19 in non-hospitalised patients: a case series - Janowitz, Tobias; Gablenz, Eva von; Pattinson, David; Wang, Timothy C.; Conigliaro, Joseph; Tracey, Kevin J.; Tuveson, David (Gut, 2020)
Objective Treatment options for non-hospitalised patients with coronavirus disease 2019 (COVID-19) to reduce morbidity, mortality and spread of the disease are an urgent global need. The over-the-counter histamine-2 receptor antagonist famotidine is a putative therapy for COVID-19. We quantitively assessed longitudinal changes in patient reported outcome measures in non-hospitalised patients with COVID-19 who self-administered high-dose famotidine orally. - Design Patients were enrolled consecutively after signing written informed consent. Data on demographics, COVID-19 diagnosis, famotidine use, drug-related side effects, temperature measurements, oxygen saturations and symptom scores were obtained using questionnaires and telephone interviews. Based on a National Institute of Health (NIH)-endorsed Protocol to research Patient Experience of COVID-19, we collected longitudinal severity scores of five symptoms (cough, shortness of breath, fatigue, headaches and anosmia) and general unwellness on a four-point ordinal scale modelled on performance status scoring. All data are reported at the patient level. Longitudinal combined normalised symptom scores were statistically compared. - Results Ten consecutive patients with COVID-19 who self-administered high-dose oral famotidine were identified. The most frequently used famotidine regimen was 80 mg three times daily (n=6) for a median of 11 days (range: 5-21 days). Famotidine was well tolerated. All patients reported marked improvements of disease related symptoms after starting famotidine. The combined symptom score improved significantly within 24 hours of starting famotidine and peripheral oxygen saturation (n=2) and device recorded activity (n=1) increased. - Conclusions The results of this case series suggest that high-dose oral famotidine is well tolerated and associated with improved patient-reported outcomes in non-hospitalised patients with COVID-19.